Synthesis, Characterization and Ionic Conductivity of Supramolecular Structure of Uracil-Functionalized PEG/LiClO4 Blend System - Rajendran, T.V.; Jaisankar, V. (Asian Journal of Chemistry, 2015)
In this paper, the synthesis and ionic conductivity behaviour of supramolecular structure based end group functionalized poly(ethylene glycol) with uracil are reported. The uracil (U) functionalized poly(ethylene glycol) (PEG), (U-PEG-U) was synthesised through Michael addition. The synthesized polymer electrolyte was characterized by Fourier-transform infrared and nuclear magnetic resonance spectral methods. Further, we described the interaction behaviour of synthesized polymer electrolyte with Li+ ions. Differential scanning calometry and FTIR studies demonstrates that the significant ability of functionalized poly(ethylene glycol) to donate its electron to coordinate with lithium ion. It is further observed that the ionic conductivity of polymer electrolyte is not only dependent on the electron donation strength of carbonyl group, but also on the molecular structure of polyester.